Cyanide-Free Silver Electrochemical Deposition on Copper and Nickel. Issue 14 (1st January 2018) - Christophe, J.; Guilbert, G.; Rayée, Q.; Poelman, M.; Olivier, M.-G.; Buess-Herman, C.
Abstract : Uracil was used as complexing agent to developp cyanide-free processes for silver deposition on copper and nickel substrates. We have highlighted that the molar ratio Ur/Ag + between uracil and silver ions concentrations and the pH are crucial in the formulation of a stable and efficient bath and were found to be equal to 4 and 13.7 respectively. Silver was deposited in a single step on copper according to a three-dimensional nucleation mechanism while silver plating of nickel substrates was found to require an additionnal silver strike step. We worked out a choline chloride – oxalic acid DES-based silver solution which allowed to obtain bright, adherent and ductile silver coatings on Ni.